Effect of particle damper technique on tribological properties during hard turning process. (2022) - Lawrance, G.; Sam Paul, P.; Joshwa, D.; Sharvilin, S.; Sudarsan, K.; Arun, R.
Abstract: In turning process, tribological properties is a significant factor that affects production in the manufacturing sector. In the present study, particle damper is used to enhance the tribological properties during turning process. A particle damper is offered by means of particle which dissipate energy through friction and inelastic collisions. A particle damper with variable material, size, and filling in a turning tool is fabricated in this work. A 27 run experiments were conducted to find the effect of particle damping on tribological properties during the turning process. The particle in the turning tool will collide with one another and increases the rigidity of the tool holder which enhances the tribological properties. The experimental results, S/N ratio and ANOVA analysis shows that when stainless steel particle is partially filled with smaller size achieve enhance tribological properties. The results were compared without particle damper and found the particle damper reduce surface roughness and tool wear effectively.